Heating pad vs. infusion warmer to prevent hypothermia in intraoperative patients: which one is more effective? - Arinjaya, I Gede Eka; Suyasa, I Gede Putu Darma; Rismawan, I Made; Suyasa, Agus Baratha (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2021)
Background: The use of heating pads and infusion warmers on intraoperative patients has been proven to prevent hypothermia. However, the differences in the effectiveness of the two methods have not been studied. Purpose: This study aims to compare the effectiveness of a heating pad and infusion warmer in preventing hypothermia (decreased body temperature and the incidence of shivering) in intraoperative patients. Methods: This research was a quasi-experimental design by a Posttest-Only Design with Nonequivalent Groups. The populations in this study were surgical patients with regional anesthesia, with a total sample of 64 respondents (32 respondents in the heating pad group and 32 respondents in the infusion warmer group) selected randomly. The incidence of hypothermia was perceived from two indicators: a decrease in body temperature and the prevalence of shivering, which was observed and recorded during the intraoperative period. The data were analyzed by discrimination tests (mean discrimination test and proportion discrimination test) to determine the difference in the effectiveness of the two groups. Results: The average decrease in body temperature during the intraoperative period (0-40 minutes of operation) in the group given the infusion warmer was greater than the group given the heating pad (p<0.001). The group given the infusion warmer was 8.750 times more likely to experience shivering than the group given the heating pad (p<0.001; OR=8.750). Conclusion: Using a heating pad is better in preventing hypothermia in intraoperative patients than using an infusion warmer.